Exploring the Association Between Gadget Use and Emotional Disturbances in Pre-School Children: Evidence from Al-Mujahidin Al-Qur'an Kindergarten - Rozeva, Shenni (Inspirasi Foundation, 2025)
Introduction: In the digital era, gadget use among preschool-aged children has become increasingly common, raising concerns about its impact on emotional development. Excessive screen time may reduce social interaction and increase emotional disturbances, such as irritability and anxiety. Objective: This study aimed to analyze the relationship between gadget use and emotional problems among preschool children at TK Al-Qur'an Almujahidin Krui in 2024. Method: A cross-sectional quantitative analytical design was used. A total of 103 children aged 4–6 years were selected through purposive sampling. Emotional problems were assessed using the Kuisioner Masalah Mental Emosional (KMME), a validated 12-item instrument. Children with diagnosed neurodevelopmental disorders were excluded. Data were analyzed using the Chi-square test and odds ratio (OR) with a significance level of p < 0.05. Results: Among the 103 participants, 26 (25.2%) had doubtful emotional problems and 77 (74.8%) exhibited deviant emotional behaviors. Children with bad gadget use were 7.71 times more likely to experience emotional problems compared to those with good gadget use (OR = 7.71, p = 0.034). A significant association was found between higher levels of gadget use and increased emotional disturbances. Conclusion: There is a statistically significant relationship between gadget use and emotional problems in preschool children. Excessive gadget use may negatively affect emotional well-being, emphasizing the need for parents and educators to monitor and regulate children’s screen time to support healthy emotional development.